SEED GERMINATION OF PEA (Pisum Sativum, L) UNDER DIFFERENT BORON CONCENTRATION LEVELS - Lima, Maria Dolores Barbosa (IRRIGA, 1998)
SEED GERMINATION OF PEA (Pisum Sativum, L) UNDER DIFFERENT BORON CONCENTRATION LEVELS Maria Dolores Barbosa Lima Escola Superior de Ciências Agrárias de Rio Verde - ESUCARV Campus Universitário - Caixa Postal 104 75901-970 - Rio Verde , Goiás 1 ABSTRACT This experiment attempted to establish the effect of irrigation with water containing different concentration of boron on the germination of pea (Pisum sativum L.), selected as a typical example of dicotyledon plants. 25 seeds were planted in aluminum trays bedded with a layer of cotton of a depth 1 cm, as a germination medium. The media was wetted to saturation with waters of varying boron concentration starting from zero B level (control treatment) up to the highest concentration of 20 (mg.dm-3) B. Germination of peas was not affected by boron concentrations up to 8 (mg.dm-3), and only slightly reduced as 20 (mg.dm-3). Once germinated, the seedling were smaller, took longer to develop and already showed toxicity symptoms when boron was applied in large doses. Hence, large amounts of boron seem to have little influence on germination, but distinct negative effects on the development of plants at the seedling stage. Keywords: irrigation, germination, boron, pea.